The continuous adverse impact of COVID-19 on temporomandibular disorders and bruxism: comparison of pre- during- and post-pandemic time periods - Tamar Shalev-Antsel; Orit Winocur-Arias; Pessia Friedman-Rubin; Guy Naim; Lihi Keren; Ilana Eli; Alona Emodi-Perlman (BMC, 2023)
Abstract Introduction Some of the conditions affected by the COVID-19 pandemic were Temporomandibular Disorders (TMD) and bruxism. The present study compares the effect of the pandemic on TMD and bruxism (sleep and awake) in three time periods: before the pandemic (pre-COV), during the pandemic (during-COV) and after the pandemic subsided (post-COVR). Material and Methods A total of 587 adult patients (108 in the pre-COV group, 180 in the during-COV group and 252 in the post-COVR group) who arrived for a routine dental treatment between October 2018 and January 2023 were evaluated according to Axis I diagnosis of the Diagnostic Criteria for Temporomandibular Disorders (DC/TMD). Each patient received a DC/TMD Axis I diagnosis as follows: (i) Painful TMD (defined by the presence of at least one of the following - local myalgia, myofascial pain with referral, arthralgia or headache attributed to TMD); (ii) Non painful TMD (defined by the presence of disc displacement with/without reduction, degenerative joint disorders and/or dislocation), (iii) Possible sleep bruxism (SB) and/or (iv) Possible awake bruxism (AB). Statistical methods Logistic regression analyses were conducted to establish the impact of time and gender on the prospects of painful TMD, non-painful TMD, SB and AB. Results The odds of subjects to be diagnosed with painful TMD at the post-COVR era were 3.3 times higher compared to the pre-pandemic time period (pre-COV, 95% C.I. 1.438-7.585). The odds of subjects to be diagnosed with non-painful TMD during-COV were 4 times higher compared to the pre-COV era (95% C.I. 1.332-12.542). The odds of subjects to present possible SB at post-COVR were 2.7 times higher compared to pre-pandemic (pre-COV, 95% C.I. 1.258-5.889, p < 0.05) and the odds to present possible AB after the pandemic subsided (post-COVR) were 3.2 times compared to the pre-pandemic period (95% C.I. 1.496-6.949). The odds of female subjects to be diagnosed with either painful or non-painful TMD were 3.7-4.4 times higher, compared to males. Conclusions Results indicate that with regard to TMD and bruxism the pandemic adverse effects persist also after COVID-19 subsides and the restrictions caused by it are abolished. Apparently, during the pandemic females were affected more seriously by painful and non-painful TMD than males.